Unimolecular chemistry of gas-phase hydrazine ions - Boulanger, Anne-Marie (University of Ottawa (Canada), 2008)
The unimolecular dissociation reactions of ionized methylhydrazine, CH 3NHNH2+·, 1,1-dimethylhydrazine, (CH 3)2NNH2+·, and tetramethylhydrazine, (CH3)2NN(CH3)2 +·, were investigated using tandem mass spectrometry, threshold photoelectron photoion coincidence spectroscopy and variational transition state theory. The modelled thresholds for the ion dissociation yielded new thermochemistry for these N2-containing ions. The low energy dissociation pathways of the methyl-substituted hydrazine radical cations correspond to the losses of a hydrogen atom, a methyl radical and/or a rearrangement process leading to the loss of methane. The three fragment ions of MH+· are ion m/z 45, CH 2NHNH2+, ion m/z 31, NHNH 2+, and ion m/z 30, N2H 2+·. The two fragment ions of DMH+· are ion m/z 59, (CH3)(CH 2)NNH2+, and ion m/z 45, CH3N=NH2+. The two fragment ions of TMH +· are ion m/z 73, (CH3)2 NNCH3+, and ion m/z 72, C 3H8N2+·. Product ion structures were determined from MIKE, CID, KER and deuterium exchange experiments performed on a modified VG ZAB mass spectrometer of BEE geometry. The TPEPICO experiments were performed at the Daresbury Laboratory Synchrotron Radiation Source. The breakdown diagrams in the threshold region for each ion were modelled. The potential energy curve of each dissociation reaction was calculated at the B3-LYP/6-31+G(d) level of theory. The molecular configuration corresponding to the minimum sum-of-states was located and used as the transition state in the RRKM calculation of k(E). The k(E) data was convoluted with the internal energy distribution of the ion, the electron transmission function of the electron analyser and the monochromator band-pass width to simulate the experimental breakdown curves. The effects of the entropy of activation on simple dissociation reactions were also investigated. Several transition states were identified with increasing ion internal energy for the methyl radical loss and the hydrogen atom loss channels. The variation in the DeltaS‡ values was found to affect largely the shape of the breakdown curves and the dissociation reactions. Enthalpies of formation of the fragment ions, determined from the theoretical fits of the experimental breakdown curves, were found to be in excellent agreement with the calculated values. The proton affinities of several NN-containing neutral molecules and the N--C and H--C bond dissociation enthalpies were also determined.
Keywords: Chemistry, Analytical.; Chemistry, Physical.